Interleukin‐13 Receptor α1–Mediated Signaling Regulates Age‐Associated/Autoimmune B Cell Expansion and Lupus Pathogenesis. Issue 9 (22nd August 2022) - Chen, Zhu; Flores Castro, Danny; Gupta, Sanjay; Phalke, Swati; Manni, Michela; Rivera‐Correa, Juan; Jessberger, Rolf; Zaghouani, Habib; Giannopoulou, Eugenia; Pannellini, Tania; Pernis, Alessandra B.
Abstract : Objective: Age‐associated/autoimmune B cells (ABCs) are an emerging B cell subset with aberrant expansion in systemic lupus erythematosus. ABC generation and differentiation exhibit marked sexual dimorphism, and Toll‐like receptor 7 (TLR‐7) engagement is a key contributor to these sex differences. ABC generation is also controlled by interleukin‐21 (IL‐21) and its interplay with interferon‐γ and IL‐4. This study was undertaken to investigate whether IL‐13 receptor α1 (IL‐13Rα1), an X‐linked receptor that transmits IL‐4/IL‐13 signals, regulates ABCs and lupus pathogenesis. Methods: Mice lacking DEF‐6 and switch‐associated protein 70 (double‐knockout [DKO]), which preferentially develop lupus in females, were crossed with IL‐13Rα1–knockout mice. IL‐13Rα1–knockout male mice were also crossed with Y chromosome autoimmune accelerator (Yaa) DKO mice, which overexpress TLR‐7 and develop severe disease. ABCs were assessed using flow cytometry and RNA‐Seq. Lupus pathogenesis was evaluated using serologic and histologic analyses. Results: ABCs expressed higher levels of IL‐13Rα1 than follicular B cells. The absence of IL‐13Rα1 in either DKO female mice or Yaa DKO male mice decreased the accumulation of ABCs, the differentiation of ABCs into plasmablasts, and autoantibody production. Lack of IL‐13Rα1 also prolonged survival and delayed the development of tissue inflammation. IL‐13Rα1 deficiency diminished in vitro generation of ABCs, an effect that, surprisingly, could be observed in response to IL‐21 alone. RNA‐Seq revealed that ABCs lacking IL‐13Rα1 down‐regulated some histologic characteristics of B cells but up‐regulated myeloid markers and proinflammatory mediators. Conclusion: Our findings indicate a novel role for IL‐13Rα1 in controlling ABC generation and differentiation, suggesting that IL‐13Rα1 contributes to these effects by regulating a subset of IL‐21–mediated signaling events. These results also suggest that X‐linked genes besides TLR7 participate in the regulation of ABCs in lupus.